Blended Learning Method in The View of Learning and Teaching Strategy in Geography Study Programs in Higher Education - Gunawan Widjaja; Aslan Aslan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
In this era of digital technology, learning is very foreign if it still uses single method methods, namely face-to-face. We firmly believe that combining traditional methods with technology must be applied to achieve outcomes, especially in postgraduate studies. For that reason, we have carried out many publications in journals, books and procedures, and other information. Then the effort has involved several steps such as understanding the data through coding evaluation and drawing conclusions that essentially want to get the answer data on this royal question as valid and accurate as possible. Based on the available evidence and the depth of the discussion of the findings, we can finally say that the learning strategy in universities, especially in the undergraduate market, is a strategy that combines the old and new ways, namely face-to-face in the classroom and is guided by collaborative learning or learning-based learning. Thus, it is hoped that the findings of this study will make the development and progress of learning and learning studies related to blended learning increase in the future.